Patients, consumers and civil society - Chambré, Susan Maizel; Goldner, Melinda (Advances in medical sociology ;, 2008)
Medical Sociology is the among the largest and first subdisciplines in Sociology. It is an area of ongoing work, advancing theory, method and our substantive understanding of social life. This series brings together the newest issues and most current concerns in Medical Sociology, in an ongoing collection of edited volumes. Each volume is edited by a medical sociologist with a particular expertise, bringing together contributions from sociologists working in different settings and nations, exploring one particular advance in Medical Sociology.